2009
DOI: 10.1182/blood-2009-02-204693
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia (CML) with P190BCR-ABL: analysis of characteristics, outcomes, and prognostic significance

Abstract: The most common BCR-ABL transcripts in chronic myeloid leukemia (CML) are e13a2(b2a2) and e14a2(b3a2). Other transcripts such as e1a2 are rare and their outcome with tyrosine kinase inhibitors (TKI) therapy is undefined. We analyzed 1292 CML patients and identified 14 with only e1a2 transcripts, 9 in chronic phase (CP), 1 in accelerated phase (AP), and 4 in blast phase (BP). Of the CP, 4 achieved complete hematologic response (CHR); 2, complete cytogenetic response (CCyR); 2, partial cytogenetic response (PCyR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 21 publications
6
117
1
1
Order By: Relevance
“…De-Lemos et al [24] reported that statistically significant difference was found for the levels of expression of transcripts b2a2 and b3a2 at six months of imatinib treatment, which shows that b2a2 may have a better molecular response than b3a2. Verma et al [25] reported that rare variants like e1a2 have an inferior response to imatinib. Sharma et al [26] found that 59% patients with b2a2 type achieved complete cytogenetic response (CGR) as compared to 28% patients with b3a2 (p = 0.04) while in 24 patients with minor or no CGR, 25% had b2a2 compared to 75% b3a2 type (p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…De-Lemos et al [24] reported that statistically significant difference was found for the levels of expression of transcripts b2a2 and b3a2 at six months of imatinib treatment, which shows that b2a2 may have a better molecular response than b3a2. Verma et al [25] reported that rare variants like e1a2 have an inferior response to imatinib. Sharma et al [26] found that 59% patients with b2a2 type achieved complete cytogenetic response (CGR) as compared to 28% patients with b3a2 (p = 0.04) while in 24 patients with minor or no CGR, 25% had b2a2 compared to 75% b3a2 type (p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…13,33 More than 95% of patients with CML have e13a2 (b2a2), e14a2 (b3a2), or both transcripts coding for p210 BCR-ABL1 tyrosine kinase, whereas only a minority express rare variants such as e1a2 transcripts, 34 which code for p190 BCR-ABL1, which is associated with rapid disease progression. Previous reports have suggested that patients with e14a2 achieve deeper molecular response to standard dose imatinib 23 and have higher platelet counts compared with patients with e13a2 transcripts.…”
Section: Bcr-abl Transcripts and Tki In CML 1273mentioning
confidence: 99%
“…A score of Ͼ 87 indicates high risk.] 102 In addition, distinct markers such as major route ACA, 15 p190 BCR-ABL , 103 and signs of acceleration may be suitable for early prediction of progression (Table 4). In addition, BMI1 and CIP2A levels at diagnosis have been reported predictive of BC.…”
Section: Can Bc Be Prevented? Is Early Prediction Possible?mentioning
confidence: 99%